2008
DOI: 10.1158/1055-9965.epi-07-0531
|View full text |Cite
|
Sign up to set email alerts
|

Statin Induces Apoptosis and Cell Growth Arrest in Prostate Cancer Cells

Abstract: Statins are a class of low molecular weight drugs that inhibit the rate-limiting enzyme of the mevalonate pathway 3-hydroxy-3-methylglutaryl-CoA reductase. Statins have been approved and effectively used to control hypercholesterolemia in clinical setting. Recent study showed statin's antitumor activity and suggested a potential role for prevention of human cancers. In this study, we did cell viability, DNA fragmentation, and terminal deoxynucleotidyl transferase -mediated dUTP nick-end labeling assays to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
141
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(157 citation statements)
references
References 32 publications
13
141
0
3
Order By: Relevance
“…3B) showed that LNCaP cells treated with d-T3 exhibited an increase in the number of apoptotic cells and the combination of d-T3 and g-Toc resulted in the onset of an especially massive apoptotic cell death. It is well known that anti-cancer activities of most anti-cancer agents mainly depend on cell cycle arrest and subsequent induction of apoptosis (20). The loss of cell cycle control in G1 has been implicated in tumor development and proliferation in prostate cancer cells (21).…”
Section: Resultsmentioning
confidence: 99%
“…3B) showed that LNCaP cells treated with d-T3 exhibited an increase in the number of apoptotic cells and the combination of d-T3 and g-Toc resulted in the onset of an especially massive apoptotic cell death. It is well known that anti-cancer activities of most anti-cancer agents mainly depend on cell cycle arrest and subsequent induction of apoptosis (20). The loss of cell cycle control in G1 has been implicated in tumor development and proliferation in prostate cancer cells (21).…”
Section: Resultsmentioning
confidence: 99%
“…Cells located in the late G 1 and G 2 -M cell cycle phases are more sensitive to radiation-induced cell death, suggesting a potential mechanism of radiosensitisation induced by statins. It is thought that statins induce cell-cycle arrest in prostate cancer cells by reducing cell proliferation and arresting these cells in the G 1 phase of the cell cycle (51)(52)(53).…”
Section: Resultsmentioning
confidence: 99%
“…Hoque et al (51) Statin induces apoptosis and cell growth Data showed that the antitumor activity of statins is due arrest in prostate cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Simvastatin induces apoptosis in human skeletal muscle cells [39] and cardiac myocytes [40], human T, B and myeloma tumor cells [41], the TR-PCT1 pericyte cell line and freshly isolated human pericytes, which surround endothelial cells in precapillary arterioles, capillaries, and postcapillary venules [42], fibroblastlike synoviocytes derived from patients with rheumatoid arthritis [43], three human prostate cancer cell lines (PC3, DU145, and LnCap) [44]. In the PC3 cell line, simvastatin induces apoptosis or necrosis depending on concentration [45].…”
Section: Human Cellsmentioning
confidence: 99%
“…Simvastatin effectively decreases cell viability in three prostate cancer cell lines (PC3, DU145, and LnCap) by inducing apoptosis and cell growth arrest at G 1 phase and inducing activation of caspase-8, caspase-3, and caspase-9 [44]. In primary cultures of human skeletal muscle cells simvastatin increases caspase-9 and caspase-3 activities up to 3-fold, induces cell apoptosis as soon as 24 h following application, and as many as 80% of cells are died 48 h later [39].…”
Section: Object Effects Of Simvastatin Refsmentioning
confidence: 99%